Hegel y Schleiermacher Encuentros y desencuentros entre dialéctica especulativa y hermenéutica - Mariano de la Maza, Luis 1955- (2008)
The proposal of this article is to show that, instead of their rivality and philosophical differences, Hegel and Schleiermacher have important points of contact, specially around the concepts of selfconsciousness and dialectics, that makes possible their common influence in Truth and Method of HansGeorg Gadamer.
Keywords: Dialéctica especulativa; Filosofía alemana; Filosofía de la religión; Filosofía del siglo XIX; Hegel; Hermenéutica; Schleiermacher